Hubungan Penerapan Bundle Ventilator-Associated Pneumonia (VAP) dengan Kejadian VAP dan Durasi Ventilator di Picu - Ana Wahyuni; Nopi Nur Khasanah; Kurnia Wijayanti (TRILOGI: Jurnal Ilmu Teknologi, Kesehatan, dan Humaniora, 2026)
Ventilator-Associated Pneumonia (VAP) is a nosocomial infection that manifests in patients following mechanical ventilation for ≥ 48 hours. This incidence significantly contributes to the escalation of morbidity, mortality, prolonged length of stay, and the financial burden of care. The implementation of the VAP Bundle as an evidence-based practice is projected to reduce VAP prevalence while optimizing the duration of ventilator use. This study aims to analyze the correlation between the implementation of the VAP Bundle and the incidence of VAP, as well as the duration of mechanical ventilation among patients in the Pediatric Intensive Care Unit (PICU) at RSUP Dr. Kariadi Semarang. This study employed a descriptive-analytic design with a cross-sectional approach. A total of 44 respondents were selected using a total sampling technique. Data were collected using VAP Bundle implementation observation sheets, medical records, and the Clinical Pulmonary Infection Score (CPIS). Data analysis was performed univariately and bivariately using the Chi-Square statistical test. The findings indicated a significant relationship between the implementation of the VAP Bundle and the incidence of VAP, as well as a relationship between the VAP Bundle implementation and the duration of ventilator use. Adherence to VAP Bundle implementation according to Standard Operating Procedures (SOP) contributed to a decrease in VAP incidence and a tendency toward a ventilator duration of ≤4 days. Compliance with the VAP Bundle protocol plays a crucial role in preventing VAP and enhancing the efficiency of ventilator use. This study recommends increasing nursing compliance with VAP Bundle standards to improve the quality of critical care nursing services.